A HIGH SPEED VACUUM CENTRIFUGE SUITABLE FOR THE STUDY OF FILTERABLE VIRUSES - Bauer, Johannes H. (The Rockefeller University Press, 1936)
1. A high speed centrifuge is described in which the speed is limited only by the strength of the material of which the rotor is made. It carries sixteen tubes, each of which conveniently accommodates 7 cc. of fluid. 2. The centrifuge operates in a very high vacuum and therefore requires only a small amount of driving energy. The arrangement has been found to eliminate the possibility of producing injurious frictional heat. 3. The rotating parts are supported by anair-bearing and are driven by compressed air. 4. The centrifuge has been successfully operated at a speed of 30,000 revolutions per minute, representing a maximum centrifugal force in the fluid of 95,000 times gravity. 5 Celluloid tubes used for centrifugation of fluid at high speeds are described. 6. Experiments are described in which good sedimentation of the yellow fever virus was obtained.